Analisis Teknik Camera Movement pada Film The Big 4 Karya Timo Tjahjanto - Eka Pebrianto Saputra; Dani Manesah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
The film The Big 4 by Timo Tjahjanto highlights the expertise in utilizing camera movement techniques that effectively support visual storytelling. This study aims to analyze various camera movement techniques, such as tracking shots, panning, and handheld shots, as well as how the combination of these techniques contributes to building the narrative, atmosphere, and emotion in the film. Through a qualitative approach using literature review, the study reveals that tracking shots are used to maintain visual continuity and enhance the intensity of action scenes, while panning helps frame the environment and provide spatial orientation to the audience. Additionally, the use of handheld shots heightens tension and realism, particularly in close combat scenes. The combination of these techniques creates a dynamic and complex visual narrative, which becomes an essential element in establishing the rhythm and mood of the story. This study concludes that the success of cinematography in The Big 4 not only delivers an engaging visual experience but also deepens the audience's emotional involvement with the characters and story. This analysis is relevant to understanding the role of cinematography in narrative development and provides insights for Indonesian filmmakers to enhance the visual and narrative quality of films.